HBM4EU chromates study – the measurement of hexavalent and trivalent chromium in exhaled breath condensate samples from occupationally exposed workers across Europe. (15th February 2023) - Leese, Elizabeth; Jones, Kate; Bocca, Beatrice; Bousoumah, Radia; Castaño, Argelia; Galea, Karen S; Iavicoli, Ivo; López, Marta Esteban; Leso, Veruscka; Ndaw, Sophie; Porras, Simo P.; Ruggieri, Flavia; et al.
Abstract: The aim of this study was to investigate the practicability of exhaled breath condensate (EBC) as a biological matrix to detect and measure hexavalent chromium (Cr(VI)) and trivalent chromium (Cr(III)) in workers occupationally exposed to Cr(VI). EBC samples were collected from workers in France, Finland, Italy, The Netherlands and the United Kingdom from three different target activities: chrome platers, stainless steel welders and surface treatment workers. Pre and post working week EBC samples were collected from 177 exposed workers and 98 unexposed workers (control group). Hyphenated chromatography systems with inductively coupled plasma – mass spectrometry (ICP-MS) were for the analysis. The results showed that the occupationally exposed workers had significantly higher levels of Cr(VI) and Cr(III) than the control group. Chrome platers exhibited the highest Cr(VI) levels in their EBC samples, with a significant increase from their pre to post samples for both Cr(VI) and Cr(III). A significant difference was also found between pre and post EBC samples for Cr(III) in welders. This study has shown that EBC has the potential to be a valid, non-invasive biological matrix to assess occupational exposure to Cr(VI) and Cr(III) for biological monitoring assessment, with the ability to detect low level inhalation exposures. Graphical Abstract: ga1 Highlights: Exhaled breath condensate (EBC) reflects tri- and hexavalent chromium in the lungs. Both chromium species were higher in EBC of workers compared to controls. Both chromium species increased from pre to post workweek EBC in chrome platers. EBC may provide lung-specific, non-invasive occupational exposure data for hexavalent chromium.